MS/MS/MS reveals false positive identification of histone serine methylation - Zhang, Junmei (2010)
Methylation of lysine and arginine residues is known to play a key role in regulating histone structure and function. However, methylation of other amino acid residues in histones has not been previously described. Using exhaustive nano-HPLC/MS/MS and blind protein sequence database searches, we tentatively assigned methylation to serine 28 of histone H3 from calf thymus. The assignment was in agreement with our stringent manual verification rules, co-elution in HPLC/MS/MS with its corresponding synthetic peptide, the dynamic nature of such methylation in distinct cell lines, and isotopic labeling. However, careful inspection of the MS/MS and MS/MS/MS spectra of a series of synthetic peptides confirmed that methylation actually occurs on K27 rather than on S28. The misassignment was caused by the fact that the (y(9) + 14) of the putative S28-methylated peptide and (b(9) + 18) ions of the K27 methylated peptide share the same m/z value (m/z 801). This MS/MS peak was used as the major evidence to assign methylation to S28 (consecutive y(8) and (y(9) + 14) ions). MS/MS/MS analysis revealed the false positive nature of serine methylation: the ambiguous ion at m/z 801 is indeed (b(9) + 18), an ion resulting from an in vitro reaction in the gas phase during collisionally activated dissociation (CAD). When lysine (K27) was acetylated, the degree of such in vitro reactions was greatly reduced, and such reactions were completely eliminated when the C-terminus was blocked by carboxylic group derivatization. Moreover, such side-chain assisted C-terminal rearrangement was found to be charge dependent. In aggregate, these results suggest that extra caution should be taken in interpretation of post-translational modification (PTM) data and that MS/MS as well as MS/MS/MS of synthetic peptides are needed for verifying the identity of peptides bearing a novel PTM.